Physicochemical and Textural Properties of Noodles Prepared from Different Potato Varieties - Kang, Jinsoo; Lee, Jungu; Choi, Moonkyeung; Jin, Yongik; Chang, Dongchil; Chang, Yoon Hyuk; Kim, Misook; Jeong, Yoonhwa; Lee, Youngseung (Preventive nutrition and food science, 2017)
This study was performed to investigate the quality characteristics of noodles made from four different potato varieties: Atlantic, Go-un, Sae-bong, Jin-sun, and wheat flour. Quality characteristics of five noodles were analyzed by general components analysis, cooking quality (rate of water absorption, cooking loss, and volume increase), and mechanical textural properties. Some variations existed in wheat- or potato-based noodles for the general components analysis, but no clear trend was observed. Higher values in the rates of water absorption, cooking loss, and volume increase were observed for the wheat flour noodle, while some variations were observed for potato noodles depending on the variety. The wheat flour noodles exhibited higher values of textural characteristics obtained from the texture profile analysis, except for adhesiveness. Higher gluten contents as well as lower ash contents in the wheat flour noodles compared to the potato noodles are thought to be the two key factors contributing to this finding.